2018
DOI: 10.1177/1077801218781931
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Bystander Intervention Among Heavy-Drinking College Men

Abstract: This study qualitatively examines how heavy-drinking college men conceptualize bystander intervention. Twelve semi-structured individual interviews were conducted with college men reporting past-month heavy drinking and sexual activity within the past 2 months. NVivo software was used to conduct a thematic analysis. Following the stage model of bystander intervention, men in this sample described situations-predominantly in drinking contexts-when other men made sexual advances toward women who were not interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 82 publications
5
46
2
Order By: Relevance
“…Contrary to Hypothesis 2, acute alcohol intoxication did not independently influence men’s speed or likelihood of intervention. This is surprising given studies of the distal effects of alcohol that suggest heavy drinking is associated with less intentions to intervene (Fleming & Wierma-Mosley, 2015; Orchowski et al, 2016) and more barriers (Oesterle et al, 2018). It is plausible that our small sample size did not allow us to capture the independent effects of acute alcohol intoxication; however, it may also be that intervention is a result of both situational and individual factors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Contrary to Hypothesis 2, acute alcohol intoxication did not independently influence men’s speed or likelihood of intervention. This is surprising given studies of the distal effects of alcohol that suggest heavy drinking is associated with less intentions to intervene (Fleming & Wierma-Mosley, 2015; Orchowski et al, 2016) and more barriers (Oesterle et al, 2018). It is plausible that our small sample size did not allow us to capture the independent effects of acute alcohol intoxication; however, it may also be that intervention is a result of both situational and individual factors.…”
Section: Discussionmentioning
confidence: 97%
“…Recent research demonstrates that heavy drinking is associated with less willingness (Orchowski et al, 2016) and a lower likelihood to intervene (Fleming & Wierma-Mosley, 2015). Further, a recent qualitative study of heavy drinking men found that men reported they would be likely to miss intervention cues when intoxicated (e.g., due to a myopic focus on more entertaining social cues) (Oesterle et al, 2018). Relatedly, an observational study examining sexual aggression intervention in a drinking context found that 79% of bystanders did not intervene (Graham et al, 2014); however, it remains unclear why bystanders were inhibited from intervening, or if they were intoxicated.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these data suggest that men who endorse the status norm may feel confident to intervene because enacting dominance over other men is consistent with their high-status masculine identity; however, they may only adopt the role of the "alpha male" if they perceive themselves being in a position of power or authority (Casey & Ohler, 2012). In line with this literature, a qualitative study of 12 college men found that men describe feeling personally responsible, and often emboldened by alcohol, to "save" a woman from the unwanted sexual advances of a male who is outside of their peer group (Oesterle, Orchowski, Moreno, & Berkowitz, 2018). This finding demonstrates that men view themselves as higher on the social hierarchy and are willing to help women who they view as needing protection (Oesterle et al, 2018).…”
Section: Masculinity and Bystander Interventionmentioning
confidence: 84%
“…In addition, the vignette in our first study described the potential victim and perpetrator as strangers to the bystander (participant). Research suggests that people are less likely to intervene on behalf of strangers than on behalf of friends (Katz et al, 2015; Palmer et al, 2018), unless the cues to danger are clear (Oesterle et al, 2018). Risk detection may work similarly; one may be more likely to recognize risk in friends or acquaintances than in strangers, especially because there would be no baseline behavior for comparison with the current behavior.…”
Section: Discussionmentioning
confidence: 99%